Comparison of Bailout and Planned Rotational Atherectomy for Heavily Calcified Coronary Lesions: A Single‐Center Experience. (19th December 2016) - Allali, Abdelhakim; Abdel‐Wahab, Mohamed; Sulimov, Dmitriy S.; Jose, John; Geist, Volker; Kassner, Guido; Richardt, Gert; Toelg, Ralph
Abstract : Objectives: The aim of this study was to compare outcomes of bailout and planned rotational atherectomy (RA) in the treatment of calcified coronary lesions. Background: Current guidelines recommend RA as a bailout procedure for calcified or fibrotic lesions that cannot be adequately dilated before stenting. Nonetheless, planned RA is sometimes performed in certain challenging anatomies. Methods: Data of patients treated with RA between 2002 and 2014 at a single‐center registry were retrospectively analyzed. The bailout RA group included patients where RA was employed after failure of balloon dilatation or stent delivery. Planned RA included patients where RA was employed electively without previous device failure. Results: The study comprised 204 patients (221 lesions) and 308 patients (338 lesions) treated with bailout or planned RA, respectively. Angiographic success was achieved in the majority of cases, but was lower in the bailout RA group (93.7% vs. 97.6%, P = 0.02). Coronary dissections occurred more frequently in the bailout RA group (8.6% vs. 4.4%, P = 0.04), mean contrast amount was higher (279 ± 135 mL vs. 202 ± 92 mL, P < 0.001), and fluoroscopy time and procedural duration were longer in that group (32 min [IQR 21–51] vs. 18 min [IQR 14–28], P < 0.001 and 111 ± 50 min vs. 76 ± 35 min, P < 0.001, respectively). In‐hospital death and myocardial infarction were not significantly different between the groups (2.9% vs. 1.3%, P = 0.21 and 6.9% vs. 4.2%, P = 0.19). In‐hospital major adverse cardiac events (MACE) were higher in the bailout RA group (10.3% vs. 5.5%, P = 0.04). The 2‐year estimated rates of MACE (25.2% vs. 28.7%, log rank P = 0.52) and its components death, myocardial infarction, and target vessel revascularization were not significantly different between the groups. Equivalence of 2‐year MACE rates was also seen in all examined subgroups. Conclusion: Shortened procedural duration and reduction of coronary dissections were observed with planned RA for selected lesions. However, this strategy does not affect long‐term clinical outcomes.